2004
DOI: 10.1002/clc.4960270503
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): New insights into mechanisms of atherogenesis and thrombosis

Abstract: Lipoprotein(a) (Lp[a]) continues to be a controversial molecule regarding its role in human vascular disease. Although the physiologic role of this molecule is still unclear, novel discoveries within the last few years have suggested numerous mechanisms whereby Lp(a) may contribute to atherosclerosis and its complications in human subjects. These effects may differentially occur in vascular tissue and circulating blood compartments. A complex interplay between tissue‐specific effects is probably more relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 112 publications
0
56
0
3
Order By: Relevance
“…1 Lipoprotein(a) can enter into human atherosclerotic plaques, 6 and results from in vitro and animal studies implicate lipoprotein(a) in foam cell formation, smooth muscle cell proliferation, and plaque inflammation and instability. 2,7,8 Lipoprotein(a) has also been shown to bind proinflammatory oxidized phospholipids recently associated with coronary artery disease. 28 Lipoprotein(a) enters into and leaves the arterial wall by mechanisms similar to LDL 3,4 and appears to accumulate more at sites of arterial injury than LDL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Lipoprotein(a) can enter into human atherosclerotic plaques, 6 and results from in vitro and animal studies implicate lipoprotein(a) in foam cell formation, smooth muscle cell proliferation, and plaque inflammation and instability. 2,7,8 Lipoprotein(a) has also been shown to bind proinflammatory oxidized phospholipids recently associated with coronary artery disease. 28 Lipoprotein(a) enters into and leaves the arterial wall by mechanisms similar to LDL 3,4 and appears to accumulate more at sites of arterial injury than LDL.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 Most but not all prospective studies of lipoprotein(a) and risk of IHD have found positive associations, 10 -16,26,27 and levels of lipoprotein(a) have also been related to severity of coronary artery disease. 29 Our risk estimates are, however, higher than those detected in the majority of previous studies.…”
Section: Kamstrup Et Al Lipoprotein(a) and Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential antithrombolytic activity has been proposed because of structural similarity with plasminogen the activity of which Lp(a) may oppose. 19 A recent editorial supported its role as a prothrombotic factor by pointing out that Lp(a) appears to be significantly associated with carotid artery occlusion but not plaque size. 20 On the contrary, there may be a stronger linkage between the kringle IV type 2 genotype and atherosclerotic stenosis in large arteries than with thrombosis in veins.…”
Section: Downloaded Frommentioning
confidence: 99%
“…20 In CRF, besides other lipid abnormalities, there is significant increase in the level of serum Lp(a). 8 Dialysis therapy may increases Lp(a) 10 or decreases Lp(a) level.…”
Section: Discussionmentioning
confidence: 99%